The effects of COVID-19-era unemployment and business closures upon the physical and mental health of older Europeans: Mediation through financial circumstances and social activity - Jason Settels; Petri Böckerman (Elsevier, 2023)
COVID-19-era lockdown policies resulted in many older persons entering unemployment, facing financial difficulties and social restrictions, and experiencing declining health. Employing the Survey of Health, Ageing and Retirement in Europe's first COVID-19 module (summer 2020) (N = 11,231) and the Karlson-Holm-Breen method for decomposition of effects within non-linear probability models (logistic regression modelling), we examined associations of pandemic-era lost work with older Europeans' (50-80 years of age) self-assessed health, depressive symptoms, and anxiety symptoms, and mediation through households' difficulties making ends meet, loneliness, and curtailed face-to-face contact with non-relatives. We find that lost work was associated with detriments in all three health outcomes. Total mediation was 23% for worsened self-assessed health, 42% for depressive symptoms, and 23% for anxiety symptoms. In all cases, combined mediation through the two social activity variables was approximately twice the magnitude of mediation through household financial difficulties. This evidence highlights the extent of employment's value for friendship formation and sustenance, and social activity, during the pandemic-era social restrictions. This might be accentuated among older persons because of the social constrictions often concomitant to advancing age. These results emphasize that the social correlates of lost employment, beyond the financial concomitants, should receive thorough research and policy attention, perhaps especially for older adults during public health crises.